OXTR methylation modulates exogenous oxytocin effects on human brain activity during social interaction. (10th February 2019) - Chen, Xu; Nishitani, Shota; Haroon, Ebrahim; Smith, Alicia K.; Rilling, James K.
Abstract : Oxytocin (OT) effects on brain function and behavior are mediated by the oxytocin receptor ( OXTR ). The distribution of OXTR in the brain can profoundly influence social behavior. Emerging evidence suggests that DNA methylation of OXTR influences OXTR expression. Previously, we conducted a pharmaco‐functional Magnetic Resonance Imaging (fMRI) study in which healthy subjects were randomized to 24 IU intranasal OT or placebo and imaged with fMRI while playing a dyadic social interaction task known as the iterated Prisoner's Dilemma (PD) game with same‐sex partners. Here, we investigate whether DNA methylation of OXTR modulates the effect of intranasal OT on the neural response to positive and negative social interactions in the PD game. OXTR methylation did not modulate OT effects within brain regions where we previously reported OT effects in response to reciprocated (caudate nucleus) and unreciprocated cooperation (amygdala and anterior insula). However, OXTR methylation did modulate OT effects on the response to both reciprocated and unreciprocated cooperation in other brain regions such as the precuneus and visual cortex. Further restricting the analysis to OXTR rs53576 GG individuals revealed that OXTR methylation modulated OT effects on the precuneus response to reciprocated cooperation in men, the lateral septum response to reciprocated cooperation in women, and the visual cortex response to unreciprocated cooperation in men. These results suggest that OXTR methylation status may influence OT effects on mentalizing, attention and reward processing during social interactions. OXTR methylation may be important to consider if exogenous OT is used to treat social behavioral disorders in the future. Abstract : OXTR methylation at CpG‐934/‐924 modulates the effect of intranasal oxytocin (INOT) on the lateral septum response to reciprocated cooperation among women with the GG genotype at OXTR SNP rs53576.